Effects of traditional Chinese exercises on cardiac rehabilitation in patients with myocardial infarction: a meta-analysis of randomized controlled trials - Zhang, Jingfang; Weng, Jieqiong; Yuan, Mengfei; Shen, Xingchen; Weng, Yayi; Shen, Xiaoxu (Frontiers in Cardiovascular Medicine, 2023)
Objective Traditional Chinese exercises (TCE) are excellent cardiac rehabilitation (CR) training that can effectively improve cardiorespiratory fitness. However, there is no published meta-analysis of TCE on CR in patients with myocardial infarction (MI). Therefore, this study aimed to provide a comprehensive evaluation from multiple perspectives. Methods This meta-analysis is based on the Cochrane Handbook of Systematic Reviews. Eight databases were searched from the date of database construction to March 15, 2023. Two investigators independently screened the literature and assessed their quality. The meta-analysis was performed with RevMan5.4 software. Results A total of 21 articles involving 1,890 patients were included. N-terminal pro-brain natriuretic peptide (NT-proBNP) in the TCE group were lower than the control group (MD = −96.34, 95%CI: −140.69 ∼−51.98, P < 0.00001, I2 = 96%), the left ventricular ejection fraction (LVEF) in the TCE group was higher than the control group (MD = 4.58, 95%CI: 3.28–5.88, P < 0.00001, I2 = 79%), the left ventricular end diastolic dimension (LVDD) in TCE group was lower than the control group (MD = −3.83, 95%CI: −5.27 ∼−2.38, P < 0.00001, I2 = 94%), the left ventricular end systolic diameter (LVESD) in TCE group was lower than the control group (MD = −2.17, 95%CI: −4.10 ∼−0.24, P < 0.00001, I2 = 96%), The 6-minute walk test (6MWT) in the TCE group was higher than the control group (MD = 69.60, 95%CI: 34.59–104.60, P < 0.00001, I2 = 99%), the oxygen uptake (VO2) in the TCE group was higher than the control group (MD = 4.38, 95%CI: 2.25–6.51, P < 0.00001, I2 = 94%), the 36-item short form survey (SF-36) in the TCE group was higher than the control group (MD = 13.34, 95%CI: 9.25–17.42, P = 0.008, I2 = 75%), the Hamilton Anxiety Scale (HAMA) in the TCE group was lower than the control group (MD = −4.34, 95%CI: −5.18 ∼−3.50, P = 1.00, I2 = 0%), the Hamilton Depression Scale (HAMD) in the TCE group was lower than the control group (MD = −3.48, 95%CI: −5.35 ∼−1.61, P = 0.0002, I2 = 88%), the incidence of major adverse cardiac events (MACEs) in the TCE group was lower than the control group (RR = 0.31, 95%CI: 0.20–0.47, P = 0.52, I2 = 0%). Subgroup analysis revealed differences in TCE types could be a potential source of heterogeneity. Conclusion MI patients who used TCE have not only notable improvements in cardiopulmonary function, physical function, quality of life, and emotions but also reduced the incidence of MACEs. Tai Chi might be more efficient than Ba Duan Jin. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023408675.